The Influence of Political Connections, Capital Intensity, and Inventory Intensity on Tax Aggressivenes - Sobirin, Hafid Alim; Purwasih, Desy (Universitas Pamulang, 2025)
This study aims to analyze the effect of Political Connection, Capital Intensity, and Inventory Intensity on Tax Aggressiveness in Consumer Non-Cyclicals Sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sampling method used in this study uses purposive sampling method, with quantitative research type. The data used is secondary data, the company's annual financial report. The number of samples used in this study were 24 companies in the in Consumer Non-Cyclicals Sector with observations for 5 (five) years, there are 120 observation objects were selected. The analysis technique used is path analysis to test the effect of intervening variable and uses the panel data regression method with the EViews version 13 application tool. The results showed that: 1) Political Connection has no affects Tax Aggressiveness, 2) Capital Intensity has affects Tax Aggressiveness, 3) Inventory Intensity has no affects Tax Aggressiveness, 4) Political Connections, Capital Intensity and Inventory Intensity have a positive and significant effect simultaneously on Tax Aggressiveness.